Teaching thinking through stories from the Qur'an using the philosophy for children method - Hendon binti Alias (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This is a case study of teaching higher order of thinking to students who have basic knowledge of the Qur'an. Philosophy for Children (Hikmah Pedagogy) was one of the methods used in teaching thinking where stories were used as the content of this study. Many of the stories used in P4C were children's literature and fables, which were written by man. This study is an effort to fill in the knowledge gaps by using stories from the Qur'an, which are divine stories. This study employed the qualitative research design and applied the exploratory case study as the research method. A small group of students aged 10 and 11 years old underwent reading and discussion sessions from lesson plans based on the research questions. Participants were from a primary school in Selangor. They were identified through purposive sampling. The homogenous sampling is a purposive sampling technique that aims for samples with similar characteristics. This study was conducted to ascertain whether the method could enhance the cognitive behaviour of the Community of Inquiry in P4C. It is also about finding barriers to the critical thinking and to see the ability amongst the students to relate present problems with the stories studied. Data collection was done using three methods: i. students posed questions based on stimuli given – stories from the Qur'an; ii. collect responses to the questions posed and discussions during the study sessions; iii. an interview with the students after the final session. The findings showed that there were some improvements in the cognitive behaviours of COI. The barriers towards critical thinking were identified, and the children became motivated to participate in the discussions. When asked about their experiences in the class, they regarded the class as enjoyable, and was different from their regular classes. They believed that they have gained more confidence as they were able to express their thoughts freely and meaningfully. This study has provided evidence on the suitability and the effectiveness of the Hikmah Pedagogy of the Philosophical Inquiry. This method should be applied throughout the curriculum.